Conversion of the geological model (fine-mesh) to a dynamic (coarse-mesh) hydrocarbon model with the nature approach in the simulation of thermal recovery in a fractured reservoir. (October 2021) - Foroozanfar, Mehdi; Rasaei, Mohammad Reza
The operation and proper management of reservoirs requires the prediction of reservoir performance. This prediction is generally done by computer simulation. Since simulation software generates static models in the number of millions and even billions, dynamic simulation on these models is difficult and sometimes impossible; therefore, multi-scale block generation is necessary. In this study, we introduce a methodology that was inspired by Earth's pattern to generate multi-scale grids on a multi-phase, heterogeneous reservoir, where the enhanced oil recovery process is steam injection. From a reservoir engineer's point of view, Earth is equivalent to a multi-scale grid model that could be a pattern for multi-scale grid generation in a hydrocarbon reservoir to minimize central processing unit time for dynamic simulation. The principle of multi-scale grid generation in hydrocarbon reservoirs is as follows: regions with a high Darcy's velocity should be fine-scale and other segments with low intensity of heterogeneity regions could resize into the up-scale. The intersection of latitude and longitude lines means that Earth's model could be a practical pattern for dynamic simulation. This intersection creates segments with fine-size blocks, like the South and North Poles, that are equal to the injection and production wells in the reservoir model and other segments that have different intensities of coarse-size blocks. Earth's magnetic field, which enters from South and exits from the North Pole, leads us to could consider Earth as a hydrocarbon model. The results of the multi-scale grid generation method, which was inspired by Earth's pattern, were compared with the fine-mesh (geological) model; the results show that the proposed method predicts with high accuracy and less run-time compared with the fine-mesh model.